Phenology-regulated defence mechanisms as drivers for Fusarium basal rot in onion (Allium cepa) - Lê, Dũng (Wiley, 2023)
Fusarium basal rot (FBR), caused by Fusarium spp., is a serious impediment for onion production. In the present study, the interaction of onion (Allium cepa) var. Takstar F1 with Allium-derived isolates of the toxigenic species F. oxysporum and F. proliferatum was investigated at seedling and bulb stage. Using a set of isolates with distinct virulence profiles, we provide evidence that the outcome of FBR is driven by the phenology of onion. Reverse transcription-quantitative PCR analysis revealed distinct expression of reliable marker genes for phenylalanine ammonia-lyase (PAL1, PAL2), lipoxygenase (LOX2), chalcone synthase (CHS), anthocyanidin synthase (ANS) and pectin methylesterases (PME) during the infection of seedlings and bulbs. These defence-related genes in seedlings were differentially expressed depending on the aggressiveness of Fusarium isolates. Despite these differential kinetics, the activated plant defence did not seem to be effective in protecting the seedlings from Fusarium infection and proliferation. Meanwhile, gene expression in the bulb organs correlated positively with FBR severity, indicating an ineffective defence response. Among the major metabolites of these Fusarium species, beauvericin was not toxic to either the seedlings or the bulbs, while fumonisin B1 appeared to be a virulence factor specific for the seedling stage. This points to differential roles of fumonisin B1 during an infection of F. proliferatum depending on the infected organ and the phenological stage of the onion host. We hypothesize that this variation, along with the differences within and between Fusarium species in terms of virulence and metabolism, contributes to the determination of disease outcome.